Investigation of teeth engagement conditions of cylindrical involute gear on contact strength, wear and durability. Part 4. Changeable interaction conditions in correlated engagement. - Чернець, М.В.; Чернець, Ю.В. (Problems of Tribology, 2015)
Chernets M.V., Chernets Ju. M. Investigation of teeth engagement conditions of cylindrical involute gear on contact strength, wear and durability. Part 4. Changeable interaction conditions in correlated engagement.According to calculation method of tooth gears’ wear and durability it has been conducted an investigation of influence of double – single – double - tooth engagement on maximal contact pressures, teeth wear and gear durability at altitude and angular correlation at changeable conditions of their contact in the result of teeth wear. It has been established the regularities of tribocontact pressures change in engagement after achievement of permissible wear depending on the values of shift coefficients and type of correlation. It has been observed the significant decrease of maximal tribicontact pressures in the input phase of double-tooth engagement. Actual gear durability after taking into account the increase of teeth contours curvature radii is 1,1 … 1,2 times higher than according to simplified method which involves constant teeth interaction conditions.